Prespektif Hukum Dan Hak Asasi Manusia Mengenai Legalisasi Narkotika Untuk Keperluan Medis - Muhammad Wahyu Harmiko (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
Narcotics abuse is a crucial problem in Indonesia As of the last few years cases of narcotics abuse continue to increase. Based on data from the National Narcotics Agency (BNN), it is found that around 3.4 million people have used narcotics throughout 2022-2023 Although narcotics are very dangerous for their users, it does not mean that the use of narcotic substances is completely prohibited. Regulations regarding the use of substances “Narcotics itself are regulated in Law Number 35 2009, which is contained in Article 7 which reads, “Narcotics can only be used for the benefit of health services and / or the development of science and technology This research is intended to determine the legal perspective and human rights regarding the use of narcotic substances for medical needs.This research uses the type of “Normative Juridical research” approach based on the main legal material by examining concepts, legal theories, legal principles and legislation related to the topic discussed. The conclusion that can be drawn from this research is that although narcotics contain harmful substances, they have benefits in the field of medicine or medical treatment even though they still have side effects. So, the laws and regulations governing the use of narcotics must be considered to ensure safety in the context of medical purposes.